The association between childhood fractures and adolescence bone outcomes: a population-based study, the Tromsø Study, Fit Futures - Christoffersen, T; Emaus, N; Dennison, E; Furberg, A-S; Gracia-Marco, L; Grimnes, G; Nilsen, OA; Vlachopoulos, D; Winther, A; Ahmed, LA (Osteoporosis International, 2017)
This is the author accepted manuscript. The final version is available from Springer via the DOI in this record Summary Childhood fracture may predict persistent skeletal fragility, but it may also reflect high physical activity which is beneficial to bone development. We observe a difference in the relationship between previous fracture and bone outcome across physical activity level and sex. Further elaboration on this variation is needed. Purpose Childhood fracture may be an early marker of skeletal fragility, or increased levels of physical activity (PA), which are beneficial for bone mineral accrual. This study investigated the association between a previous history of childhood fracture and adolescent bone mineral outcomes by various PA levels. Methods We recruited 469 girls and 492 boys aged 15–18 years to this study. We assessed PA levels by questionnaire and measured areal bone mineral density (aBMD) and bone mineral content (BMC) using dual-energy X-ray absorptiometry (DXA) at arm, femoral neck (FN), total hip (TH), and total body (TB) and calculated bone mineral apparent density (BMAD, g/cm3). Fractures from birth to time of DXA measurements were retrospectively recorded. We analyzed differences among participants with and without fractures using independent sample t test. Multiple linear regression was used to examine the association between fractures and aBMD and BMC measurements according to adolescent PA. Results Girls with and without a previous history of fracture had similar BMC, aBMD, and BMAD at all sites. In multiple regression analyses stratified by physical activity intensity (PAi), there was a significant negative association between fracture and aBMD-TH and BMC-FN yet only in girls reporting low PAi. There was a significant negative association between forearm fractures, BMAD-FN, and BMAD-arm among vigorously active boys. Conclusion Our findings indicate a negative association between childhood fractures and aBMD/BMC in adolescent girls reporting low PAi. In boys, such an association ...